Improved Electrical Properties and Reliability of GaAs Metal–Oxide–Semiconductor Capacitor by Using LaAlON Passivation Layer. Issue 9 (26th July 2017) - Liu, Li Ning; Choi, Hoi Wai; Xu, Jing Ping; Lai, Pui To
Abstract : GaAs metal–oxide–semiconductor (MOS) capacitors with NbAlON gate dielectric are fabricated with LaAlON or LaON as interface passivation layer and compared with their counterpart without interface passivation layer. Experimental results show that improvements in electrical properties and reliability are achieved, especially for the sample with LaAlON passivation layer (the hygroscopicity of LaON is largely reduced by Al incorporation): relatively high k value (25.5), low interface‐state density (6.8 × 10 11 cm −2 eV −1 ), small flatband voltage (0.67 V), small hysteresis (45 mV), small frequency dispersion and low gate leakage (6.18 × 10 −6 A cm −2 at V fb + 1 V). These should be attributed to the suppressed growth of unstable Ga and As oxides on the GaAs surface and reduced in‐diffusion of elements from the gate dielectric to the GaAs surface by the LaAlON passivation layer during gate‐dielectric annealing. Abstract : LaAlON as interfacial passivation layer for GaAs MOS applications with NdAlON gate dielectric is proposed and investigated. Combining the advantages of AlON and LaON in passivating GaAs surface, LaAlON can effectively suppress the growth of unstable GaAs native oxide and reduce in‐diffusion of elements from the gate dielectric to the substrate, and thus achieves high performance.